Reducing soil acidity in ultisols and oxisols using red gypsum and biochar in Malaysia - Zannah, Talha Ibrahim (2017)
The accruing benefits from RG, rich in Ca and S, produced in over 400,000 tonnes, yearly in Malaysia, can impact positively on the overall growth of crops by providing a readily soluble form of calcium, which is a principal problem in the Malaysian tropical soils. Biochar has 4.49 million ha under oil palm plantation, this connotes huge amount produced yearly. The pursuits to boost food production, the maize grown on these soils which have been below optimal yield are unsatisfactory due to the acid infertility. Therefore, the underlying hypothesis was that red gypsum and/or biochar application can impact positively or negatively on soil chemical properties and productivity of maize crop. The studied soils are representative of Peninsular Malaysia Ultisols and Oxisols comprising four Series, two from each taxonomic class. A series of experiments were conducted in laboratory, greenhouse and in the field to determine i) the effects of sulphate adsorption on pH and the charge properties of Ultisols and Oxisols ii) Al and Mn toxicity in the soils using red gypsum in combination with biochar and iii) the effects of red gypsum application on the growth of maize. Sulphate adsorption capacities differ among soil studied due to variation in physical and chemical properties. Four t ha-1 RG incorporation significantly (P < 0.05) increased sulphate adsorption from 22 to 456, 38 to 526, 28 to 474, 70 to 516 mg kg-1 in Bungor, Kuala Brang, Segamat and Kuantan Series respectively, raising soil pH from 4.5 to 5.2 and 4.9 to 5.5 with significant reduction in the activities of Al and Mn in the soil solution from 9.3 to 1.0 and 10.1 to 2.0 μM in Segamat and Kuantan Series, lowering PZC by 0.6 digits in Kuantan Series. Five t ha-1 biochar application significantly increased the sulphate adsorption from 22 to 138, 38 to 170, 28 to 358, 70 to 180 mg kg-1, raising pH from 4.4 to 4.9, 3.9 to 4.5, 4.5 to 5.3 and 4.9 to 5.7 in Bungor, Kuala Brang, Segamat and Kuantan Series respectively, lowering the PZC by 0.2 to 0.3 digits in Bungor, Kuala Brang and Segamat Series, with significantly decreased Al and Mn activities in all the soil studied. The 3 t ha-1 RG + 2 t ha-1 biochar incorporation significantly (P < 0.05) increased sulphate adsorption from 22 to 458, 38 to 494, 28 to 494, 70 to 542 mg kg-1 in Bungor, Kuala Brang, Segamat and Kuantan Series respectively, significantly, raising pH from 3.9 to 4.6, 4.5 to 5.4 to 5.8 in Kuala Brang, Segamat and Kuantan Series due to significant reduction in Al activity, lowering the PZC by 0.6 digits in Kuala Brang and Segamat Series. Calcium levels increased significantly due to respective application of 4, 5 and 3 + 2 t ha-1 RG, biochar and RG + biochar. Both RG and biochar playing a substantial role in reducing toxicities of Al and Mn. The mechanism for the adsorbed sulphates involves both specific and non-specific adsorption processes. Incorporation of red gypsum and/or biochar into the acid soils improved maize growth. The red gypsum treated soils had significantly increased the biomass of the maize crop, which ranged from 17 to 45 g plant-1 in the greenhouse experiment, in Kuala Brang and Kuantan Series. This had contributed 66 and 78 % to the growth of maize crop. The RG and biochar had significant effects on maize growth (761 to 1309 g plot-1) as an amendment under field condition on Bungor Series. In addition to the discrete soil characteristics in terms of nutrient supply, the biomass in the RG amended soils was significantly positively related to available P, exchangeable Ca, Mg and K but negatively related to soil exchangeable Al and Mn (P < 0:05). The reduction in acidity by red gypsum was due to increased exchangeable Ca contents.